ANALYSIS OF BILLBOARD CONTRIBUTION TAX TO REGIONAL INCOME OF SUKOHARJO DISTRICT IN YEAR 2012-2016 - Suhesti Ningsih (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2017)
The purpose of this study was to determine the level of contribution of the advertisement tax on revenue, which in the era of regional autonomy, local governments are required to always improve the reception area, such as an increase in local tax revenue through advertising tax receipts. This research applies descriptive analysis method, wherein the method is used to provide a systematic explanation, actual and accurate statement of fact, and just describe situations or events not to seek or explain the relationships and testing hypotheses. From the analysis of the data shows that Sukoharjo advertisement tax revenue from the year 2012-2016 reached an average of 119.02%.Advertisement tax contribution rate to the Local Tax reached an average3.06%, to the level of the advertisement tax revenue contribution to the local revenue of the year 2012-2016 is still in very less criteria with an average 1.50%.